Socio-Demography and risk factor evaluation of ischemic stroke in Neurology department of a Tertiary Care Hospital: A Cross-Sectional Study - Khan, Nurul Amin; Wadud, Shaheen; Islam, Torikul; Das, Probalkanti; haq, Enamul (Journal of Dhaka National Medical College & Hospital, 2018)
Stroke is the commonest neurological emergency and leading cause of death and disability. It is the third leading cause of death in Bangladesh. A total number of 60 clinically and CT confirmed acute ischemic stroke patients were selected from Neurology department Dhaka National Medical College and Hospital (DNMCH) and socio demographic and major risk factors among acute ischemic CVD patients were identified and correlated. It was a hospital based observationalcross-sectional study in DNMCH. The mean age of study population was 64.14 years, 68% were male and 32% were female. Among them 60% were illiterate and of the literate around 27% went to primary school about 7% completed SSC, 3% completed HSC and around 3 % graduated and above. Most of the patient were businessman (40%), others were house wife (10%), service (5%), Farmer (3%), among them sedentary workers 53.3% and moderate worker 46.6%. On evaluation of major risk factors 80% of patient had history of hypertension, 70% previous TIA, 50% dyslipidemia,46.6% smoking, 43.3% ischemic heart disease, 36.6% Diabetes mellitus, 36.6% advanced age, 13.3% carotid stenosis, 10% valvular heart disease and OCP took 6 % of patients. J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 40-43